About the isoperimetric property of λ-convex lunes on the Lobachevsky plane - Drach, K.D. (Reports of the National Academy of Sciences of Ukraine, 2014)
We give a sharp lower bound of the area of a domain that can be enclosed by a closed embedded λ-convex curve of a given length on the Lobachevsky plane.